How European American and Taiwanese Mothers Talk to Their Children About Learning. Issue 3 (9th October 2013) - Li, Jin; Fung, Heidi; Bakeman, Roger; Rae, Katharine; Wei, Wanchun
Abstract : Little cross‐cultural research exists on parental socialization of children's learning beliefs. The current study compared 218 conversations between European American and Taiwanese mothers and children (6–10 years) about good and poor learning. The findings support well‐documented cultural differences in learning beliefs. European Americans mentioned mental activities and positive affect more, whereas Taiwanese mentioned learning virtues and negative affect more. Mothers, especially European American, reciprocated their children's talk about mental activities, learning virtues, and negative affect. Children, especially Taiwanese, reciprocated their mother's talk about positive affect. Mothers invoked more mental activities and positive affect when discussing good learning, but more learning virtues and negative affect when discussing poor learning. These findings reveal a source of cultural differences in beliefs and potential enculturation.